Using Systematic Reviews to Support Future Dietary Reference Intakes: A Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In response to a request from the US Department of Agriculture, the Health and Medicine Division (HMD) of the National Academies established the Standing Committee to Review the Dietary Reference Intake (DRI) Framework. The committee was asked to respond to DRI-related questions to inform the Federal DRI working group about the conduct of new DRI reviews and DRI-related issues more broadly, including their application.
Keywords: Food and Nutrition

Finding What Works in Health Care: Standards for Systematic Reviews - Institute of Medicine (The National Academies Press, 2011)
Healthcare decision makers in search of reliable information that compares health interventions increasingly turn to systematic reviews for the best summary of the evidence. Systematic reviews identify, select, assess, and synthesize the findings of similar but separate studies, and can help clarify what is known and not known about the potential benefits and harms of drugs, devices, and other healthcare services. Systematic reviews can be helpful for clinicians who want to integrate research findings into their daily practices, for patients to make well-informed choices about their own care, for professional medical societies and other organizations that develop clinical practice guidelines.
Keywords: Health and Medicine

Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report provides input into the design of an Agency for Healthcare Research and Quality (AHRQ) systematic review of evidence on effective care-related interventions for people with dementia and their caregivers. This letter report describes potential changes and considerations for the key questions and study design that would result in the most informative and timely evidence review on this topic.
Keywords: Health and Medicine

Considerations for the Design of a Systematic Review of Interventions for Preventing Clinical Alzheimer’s-Type Dementia, Mild Cognitive Impairment, and Age-Related Cognitive Decline: Letter Report - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The National Institutes of Health - and many other organizations and individuals worldwide - are interested in the state of the science on preventing Alzheimer’s disease, mild cognitive impairment, and age-related cognitive decline. This letter report reviews the evidence on interventions to decrease the risk of developing clinical Alzheimer’s-type dementia and mild cognitive impairment, and delay or slow age-related cognitive decline. It also makes recommendations that inform public health messaging on preventative interventions and recommendations for future research.
Keywords: Health and Medicine

Review of NASA's Space Flight Health Standards: Letter Report - Institute of Medicine (The National Academies Press, 2007)

Year in Review 2023: Roundtable on Obesity Solutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
During 2023, the Roundtable on Obesity Solutions remained committed to reducing the prevalence of obesity by working across systems and sectors and maintaining a focus on structural racism, bias and stigma, and health communication. Framing their activities and discussions within these three areas, the roundtable and its five Innovation Collaboratives covered important and timely issues, including exploring the strengths and limitations of body mass index and other measures of body composition and body fat distribution, and strategies for improving communication about body weight. This annual report summarizes the activities of the roundtable in 2023.
Keywords: Food and Nutrition

Roundtable on Obesity Solutions: Year in Review 2022 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
During 2022, the Roundtable on Obesity Solutions continued to implement its strategic plan and resulting systems map as a way of informing its activities and publications. The roundtable's main objective for the year was to utilize new ideas and perspectives from the actions and outputs from this foundational work in order to pursue actionable solutions that leverage the multisector perspectives of the roundtable members while continuing a focus on dissemination. The three identified priority focus areas (structural racism, biased mental models and social norms, and health communication) continue to provide an important lens through which the roundtable has framed its activities and discussions, as well as for the roundtable's five Innovation Collaboratives. This annual report summarizes the activities of the roundtable in 2022.
Keywords: Food and Nutrition

Peer Review of a Report on Strategies to Improve Patient Safety - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
In response to a congressional mandate under the Patient Safety and Quality Improvement Act of 2005, the National Academies of Sciences, Engineering, and Medicine was asked to review the Agency for Healthcare Research and Quality (AHRQ) draft report Strategies to Improve Patient Safety: Draft Report to Congress for Public Comment and Review by the National Academy of Medicine. The National Academies convened a committee of four subject-matter experts with experience in clinical patient safety, patient-safety research, health information technology, safety science, clinical medicine, and implementation science to conduct a peer review of the draft report. This committee had less than three months to review the AHRQ draft report and comment on additional effective strategies for improving patient safety, new evidence of effectiveness for safety strategies, potential implementation methods that were not mentioned, and any general technical corrections. The Patient Safety and Quality Improvement Act of 2005 created valuable national resources as part of the tools needed for systemic change. The committee offers these additional strategies to improve patient safety for consideration in the revision of the AHRQ draft report to Congress.
Keywords: Health and Medicine

Review of the Department of Veterans Affairs Presumption Decision Process - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Department of Veterans Affairs (VA) provides health care and other benefits to eligible veterans with physical and mental injuries or illnesses (conditions) related to their military service. When the scientific information needed to connect a veterans service or a particular military exposure with their diagnosed condition is nonexistent, impossible to obtain, or incomplete, VA may make a presumption of service connection using a formalized decision process. In 2022, VA instituted a series of changes intended to ensure the presumption decision process was more scientifically based, fair, consistent, transparent, timely, and veteran-centric. The PACT Act of 2022 called for a National Academies committee to review the VA revised process document used to identify medical conditions to evaluate for presumption status, the factors that such an evaluation entails, and the governance process for the review and approval of a presumption recommendation. This resulting report, Review of the Department of Veterans Affairs Presumption Decision Process, contains the committee findings, conclusions, and recommendations.
Keywords: Health and Medicine

Review of Four CARA Programs and Preparing for Future Evaluations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The Comprehensive Addiction and Recovery Act (CARA; P.L. 114-198) was signed into law in 2016 to help address the challenges of overdose deaths and opioid use disorder, and to expand access to evidence-based treatment. Among these efforts was the authorization of four grant programs to be overseen by the Substance Abuse and Mental Health Services Administration (SAMHSA). In 2018, SAMHSA requested that the National Academies establish a committee to conduct a review of the four programs, which focus primarily on opioids, but occasionally include treatment and recovery services for co-occurring substance use disorders. The review resulted in three consensus study reports over five years. This third and final report aims to (1) understand the processes of the four grant programs; actions taken by grantees and their partners; impacts to clients, patients, the community, and public; and structural or environmental changes that might have resulted from grant funding, and (2) analyze how future congressionally mandated evaluations can be structured and carried out to better support policy makers.
Keywords: Health and Medicine

Building Data Capacity for Patient-Centered Outcomes Research: Interim Report 2–Data Standards, Methods, and Policy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Office of the Assistant Secretary for Planning and Evaluation (ASPE), in partnership with other agencies and divisions of the United States Department of Health and Human Services, coordinates a portfolio of projects that build data capacity for conducting patient-centered outcomes research (PCOR). PCOR focuses on producing scientific evidence on the effectiveness of prevention and treatment options to inform the health care decisions of patients, families, and health care providers, taking into consideration the preferences, values, and questions patients face when making health care choices. ASPE asked the National Academies to appoint a consensus study committee to identify issues critical to the continued development of the data infrastructure for PCOR. The committee's work will contribute to ASPE's development of a strategic plan that will guide their work related to PCOR data capacity over the next decade. As part of its information gathering activities, the committee organized three workshops to collect input from stakeholders on the PCOR data infrastructure. This report, the second in a series of three interim reports, summarizes the discussion and committee conclusions from the second workshop, focused on data standards, methods, and policies that could make the PCOR data infrastructure more useful in the years ahead. Participants in the workshop included researchers and policy experts working in these areas.
Keywords: Computers and Information Technology; Health and Medicine; Behavioral and Social Sciences

Forum on Drug Discovery, Development, and Translation: 2021 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2021, the National Academies' Forum on Drug Discovery, Development, and Translation (the forum) hosted a four-part public workshop, Envisioning a Transformed Clinical Trials Enterprise: Establishing an Agenda for 2030, to set goals for the clinical trial enterprise in the year 2030 and chart a path toward those goals. The forum also completed a three-part public workshop, Innovation in Drug Research and Development for Prevalent Chronic Diseases, which brought together stakeholders to address barriers to spurring innovation for drug research and development for highly prevalent chronic diseases. Together with the National Cancer Policy Forum and the Forum on Aging, Disability, and Independence, the forum convened a three-day public workshop to identify opportunities to improve the evidence base on the effectiveness and safety of cancer therapies in adults across the older age span. For more information, please visit the forum webpage.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2023 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In 2023, the Forum on Drug Discovery, Development, and Translation focused on diverse topics, including approaches to define and evaluate in-home drug disposal systems for opioid analgesics, the diagnosis and treatment of adults with attention-deficit/hyperactivity disorder and implications for drug development, strategies to optimize public–private partnerships for clinical cancer research, opportunities to prepare the future workforce in research and development, and other policy updates relevant to drug discovery, development, and translation. Learn more in this 2023 Annual Review.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 10 Year Review: 2011-2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
This special edition Ten-Year Review takes a look back at some of the most influential work of the National Academies' Forum on Drug Discovery, Development, and Translation over the past decade. In November 2011, amid growing concerns about the future of the U.S. clinical trials enterprise and its competitiveness on the global stage, the forum convened a public workshop for stakeholders to lay out a vision for a transformed clinical trials enterprise in the United States by 2020. This workshop laid the foundation for a variety of forum activities focused on the following thematic priorities:
Keywords: Health and Medicine

Scanning for New Evidence on Riboflavin to Support a Dietary Reference Intake Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Dietary Reference Intakes (DRIs) are a set of evidence-based nutrient reference values for intakes that include the full range of age, gender, and life stage groups in the US and Canada. At the request of the U.S. Department of Agriculture, Agricultural Research Service and the U.S. Department of Health and Human Services, Food and Drug Administration, Center for Food Safety and Applied Nutrition, the National Academies of Science, Engineering, and Medicine convened an ad hoc committee to carry out a literature search and evidence scan of the peer-reviewed published literature on indicators of nutritional requirements, toxicity, and chronic disease risk reduction for riboflavin. Scanning for New Evidence on Riboflavin to Support a Dietary Reference Intake Review builds on the methodology for evidence scanning nutrients (which have existing DRIs) to determine whether there is new and relevant knowledge available that may merit a formal reexamination of DRIs for riboflavin. This report offers comments on the methodological approach to the evidence scan and discusses its findings and interpretation of the process to provide the study sponsors with a greater context to support their interpretation and application of the reported results.
Keywords: Food and Nutrition

Evidence Review of the Adverse Effects of COVID-19 Vaccination and Intramuscular Vaccine Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Vaccines are a public health success story, as they have prevented or lessened the effects of many infectious diseases. To address concerns around potential vaccine injuries, the Health Resources and Services Administration (HRSA) administers the Vaccine Injury Compensation Program (VICP) and the Countermeasures Injury Compensation Program (CICP), which provide compensation to those who assert that they were injured by routine vaccines or medical countermeasures, respectively. The National Academies of Sciences, Engineering, and Medicine have contributed to the scientific basis for VICP compensation decisions for decades. HRSA asked the National Academies to convene an expert committee to review the epidemiological, clinical, and biological evidence about the relationship between COVID-19 vaccines and specific adverse events, as well as intramuscular administration of vaccines and shoulder injuries. This report outlines the committee findings and conclusions.
Keywords: Health and Medicine

Rapid Expert Consultation on Staffing Considerations for Crisis Standards of Care for the COVID-19 Pandemic (July 28, 2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This rapid expert consultation builds on prior National Academies reports on the Crisis Standards of Care (CSC) and the rapid expert consultation on March 28, 2020, and focuses on staffing needs for the care of COVID patients, including the deployment and allocation of expert clinical staff during COVID-19. It does not attempt to dictate exactly what choices should be made under exactly what circumstances, as that should be left to the judgment of the professional, institutional, community, and civic leaders who are best situated to understand the local conditions.
Keywords: Health and Medicine

Rapid Expert Consultation on Crisis Standards of Care for the COVID-19 Pandemic (March 28, 2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This rapid expert consultation responds to a request from the Office of Science and Technology Policy (OSTP) concerning the implementation of crisis standards of care (CSC) in response to the COVID-19 outbreak. Building on a 10-year foundation of work by the Institute of Medicine, this document summarizes the broad principles and core elements of CSC planning and implementation. The National Academies of Sciences, Engineering, and Medicine convened a standing committee of experts to help inform OSTP on critical science and policy issues related to emerging infectious diseases and other public health threats. The standing committee includes members with expertise in emerging infectious diseases, public health, public health preparedness and response, biological sciences, clinical care and crisis standards of care, risk communication, and regulatory issues.
Keywords: Health and Medicine

2021 Year in Review: Roundtable on Obesity Solutions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Keywords: Food and Nutrition

The Clinical Utility of Compounded Bioidentical Hormone Therapy: A Review of Safety, Effectiveness, and Use - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The U.S. Food and Drug Administration (FDA) has approved dozens of hormone therapy products for men and women, including estrogen, progesterone, testosterone, and related compounds. These products have been reviewed for safety and efficacy and are indicated for treatment of symptoms resulting from hormonal changes associated with menopause or other endocrine-based disorders. In recent decades, an increasing number of health care providers and patients have turned to custom-formulated, or compounded, drug preparations as an alternative to FDA-approved drug products for hormone-related health concerns. These compounded hormone preparations are often marketed as "bioidentical" or "natural" and are commonly referred to as compounded bioidentical hormone therapy (cBHT).
Keywords: Health and Medicine